2011
DOI: 10.1155/2011/160867
|View full text |Cite
|
Sign up to set email alerts
|

Interventional Radiology and the Care of the Oncology Patient

Abstract: Interventional Radiology (IR) is occupying an increasingly prominent role in the care of patients with cancer, with involvement from initial diagnosis, right through to minimally invasive treatment of the malignancy and its complications. Adequate diagnostic samples can be obtained under image guidance by percutaneous biopsy and needle aspiration in an accurate and minimally invasive manner. IR techniques may be used to place central venous access devices with well-established safety and efficacy. Therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 97 publications
(130 reference statements)
0
16
0
Order By: Relevance
“…8,13 Furthermore, in some studies the incidence of cholangitis in patients with underlying malignancy has been shown to be approximately 50% in total; in particular, it is twice as common in those with internal and external drainage than in those with external drainage alone. 2,22 In addition, it has been shown that the longer the duration of PBD, the more likely the patient is to develop cholangitis. 2,23 Infected bile has been detected in 25% to 36% of patients with malignant biliary obstruction, 24 making pre-procedural administration of appropriate prophylactic antibiotics to this group of patients even more important; and overall, prophylactic antibiotic, including cover for Escherichia coli, Klebsiella, Enterococcus, Streptococcus, Enterobacter and Pseudomonas aeruginosa, is strongly recommended for all patients prior to biliary procedures, to minimise the risk of potential septic complications.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…8,13 Furthermore, in some studies the incidence of cholangitis in patients with underlying malignancy has been shown to be approximately 50% in total; in particular, it is twice as common in those with internal and external drainage than in those with external drainage alone. 2,22 In addition, it has been shown that the longer the duration of PBD, the more likely the patient is to develop cholangitis. 2,23 Infected bile has been detected in 25% to 36% of patients with malignant biliary obstruction, 24 making pre-procedural administration of appropriate prophylactic antibiotics to this group of patients even more important; and overall, prophylactic antibiotic, including cover for Escherichia coli, Klebsiella, Enterococcus, Streptococcus, Enterobacter and Pseudomonas aeruginosa, is strongly recommended for all patients prior to biliary procedures, to minimise the risk of potential septic complications.…”
Section: Discussionmentioning
confidence: 99%
“…2,22 In addition, it has been shown that the longer the duration of PBD, the more likely the patient is to develop cholangitis. 2,23 Infected bile has been detected in 25% to 36% of patients with malignant biliary obstruction, 24 making pre-procedural administration of appropriate prophylactic antibiotics to this group of patients even more important; and overall, prophylactic antibiotic, including cover for Escherichia coli, Klebsiella, Enterococcus, Streptococcus, Enterobacter and Pseudomonas aeruginosa, is strongly recommended for all patients prior to biliary procedures, to minimise the risk of potential septic complications. 2,10 Previously recommended prophylaxis regimens included ampicillin and gentamycin or cefotetan and mezocillin 25 ; however, in Beaumont Hospital, the prophylactic antibiotic of choice is monotherapy with piperacillin/tazobactam (Tazocin, Pfizer, Cork, Ireland), which is a broad-spectrum antibiotic that has Gram-negative, Gram-positive, and aerobic coverage, and importantly, high levels of biliary excretion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations